Assessing Attitudes of the Youth Towards the Elderly - Josephine Wabibye (Uganda Christian University, 2024)
This study aimed to assess the attitudes of the youths towards the elderly in Kauga Village, Mukono Municipality and to examine its impact on the wellbeing of older individuals. The general objective was to explore the interplay between youths attitudes and the quality of life of the elderly. A mixed-methods strategy was used in the research, employing both quantitative and qualitative data. Interviews were carried out with youth, the elderly, and important stakeholders in Kauga Village. The results of the study showed that young people's opinions significantly affect older folks' wellness, with positive attitudes resulting in higher levels of social support and involvement. On the other hand, loneliness and a lack of support were linked to negative sentiments. The study showed how crucial it is to comprehend young people's perspectives in order to foster social interaction and deal with interpersonal problems. In order to foster collaboration and respect amongst generations, it underlined the necessity of focused interventions and educational initiatives. Potential bias from self reported data as well as issues with representatives and resource availability were among the study shortcomings. Despite these limitations the study offered valuable data about the nature of the youth elder interactions in Kauga Village and presents a conceptual structure for formulating plans for creating age and inclusive community development initiatives.